2016
DOI: 10.1016/j.mre.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Ion stopping in dense plasmas: A basic physics approach

Abstract: We survey quite extensively the present research status of ion-stopping in dense plasmas of potential importance for initial confinement fusion (ICF) driven by intense and heavy ion beams, and also for warm dense matter (WDM). First, we put emphasis on every possible mechanism involved in the shaping of the ion projectile effective charge, while losing energy in a target plasma with classical ions and partially degenerate electrons. Then, we switch to ion stopping by target bound electrons, taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…This kind of experimental scenario allows for precise measurement of intense proton beam stopping in dense ionized matter. We observed that the energy loss is enhanced by one order of magnitude in comparison to the predictions from individualproton stopping theories, Bethe-Bloch 28,29 , Li-Petrasso (LP) 26 , standard stopping model (SSM) 32 . Through PIC simulation, we attribute the high degree of enhancement to a strong decelerating electric field induced by the intense proton beam.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…This kind of experimental scenario allows for precise measurement of intense proton beam stopping in dense ionized matter. We observed that the energy loss is enhanced by one order of magnitude in comparison to the predictions from individualproton stopping theories, Bethe-Bloch 28,29 , Li-Petrasso (LP) 26 , standard stopping model (SSM) 32 . Through PIC simulation, we attribute the high degree of enhancement to a strong decelerating electric field induced by the intense proton beam.…”
mentioning
confidence: 79%
“…Since the discovery of alpha decay and the availability of energetic fission fragments, it became interesting to study fast particle stopping processes in matter [20][21][22][23][24][25] . In past decades, numerous theoretical models [26][27][28][29][30][31][32] , some of which can be considered to be further developments of the early work of Bethe 28 and Bloch 29 , are built to describe individual charged particle stopping in dense ionized matter. Only recently experiments with sufficient precision were carried out with dense ionzied matter to distinguish between different models 25,[33][34][35] .…”
mentioning
confidence: 99%
“…The interaction of heavy charged particles with matter is of importance in various fields of physics. While fundamental work dates back to the scattering and stopping of fission fragments, [1] renewed interest is due to progress in (cosmic) high-energy and fusion physics using accelerators and detectors, for example, References 2, 3, due to ion stopping in dense plasmas [4] and due to advances in material science and technology. Concerning the latter, particularly ion beams are nowadays frequently used in the fabrication and control of microelectronic devices, [5] in mass spectrometers [6,7] and in radiation diagnostics and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the high compression regime, we have to deal with degenerate matter. Energy loss of charged particles in degenerate matter is practically unexplored . An alternative to intense laser beams is intense, high‐energy, heavy ion beams.…”
Section: Introductionmentioning
confidence: 99%
“…Energy loss of charged particles in degenerate matter is practically unexplored. [13] An alternative to intense laser beams is intense, high-energy, heavy ion beams. They can be produced efficiently, with a conversion efficiency of electric power to kinetic energy of more than 20%.…”
mentioning
confidence: 99%